Study on components match of solar-ground source heat pump and heating network complementary heating system in severe cold region - Hao, Hong; Zhao, X.; Feng, G.; Xue, X. (2014)
The typical building in severe cold region was selected. The form of the complementary heating system on solar-ground source heat pump and heating network was proposed in this paper. The simulation model of the complementary system was established by TRNSYS which is transient simulation software as design platform. The various components were designed. The matching relationship among the components which including the solar collector and the ground heat exchanger and the storage tank and the heating network were researched. The results of the simulation demonstrate that the average COP of the heat pump unit is 4.04, and monthly average COP is 4.0 or more. The heat taken from the soil is reduced by 30 % in the auxiliary role of solar. Under the same of supplying heat, when the area of solar collector is increased by every 1 m2, and the length of ground heat exchanger can be approximately decreased by 5.6 m. When the matching relationship of the volume of the storage tank and the solar collector area is 60-80 L/m, and the efficiency of the water tank is highest in the solar short-term heat storage system. © Springer-Verlag Berlin Heidelberg 2014.